PERLINDUNGAN KESELAMATAN KERJA TERHADAP PEKERJA TEKNISI DI PT. ZI VISION PANGKALAN KERINCI - Willy Ponco; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Health and Safety (K3) is a program created for the workers / laborers and businessmen as prevention (preventive) if onset occupational accidents and diseases caused by working relationships within the work environment by identifying them on things that berpontensi cause of occupational accidents and diseases as a result of the relationship employment and anticipatory measures in case of such. It should be noted that the idea of the Occupational Health and Safety (K3) has existed since 20 years ago, but until now there are workers / laborers and companies who do not understand the correlation Occupational Health and Safety (K3) with an increase in the company's performance, do not even know the rules The.The purpose of this study to find out why the technician in PT. Zi Vision does not use personal protective equipment in accordance with the Regulation of the Minister of Manpower and Transmigration Republic of Indonesia Number per.08 / Men / VII / 2010. And to identify barriers and what is being done PT. Zi Vision in implementing the use of Personal Protective Equipment (PPE) against workers technicians.In this study, the authors use the method of sociological approach is done by conducting research directly in the field with the aim of collecting data that an interviews and a literature review were then referred to as primary data. Then analyzed and compared with the existing regulations.Based on the results of the study can be drawn a conclusion that the technicians who do not use personal protective equipment in because of the discomfort of workers while using personal protective equipment when working, is clear that the workforce has violated the rules - the rules that exist, such as the Minister of Manpower and Transmigration No. 8 / MEN / VII / 2010 and Law No. 1 of 1970 About Safety.Key words: Safety and Health at Work - Personal Protective Equipment